Coping with Childbirth: Brain Structural Associations of Personal Growth Initiative - Mangelsdorf, Judith (Frontiers in Psychology, 2017)
Major life events require psychological adaptations and can be accompanied by brain structural and functional changes. The goal of the current study was to investigate the association of Personal Growth Initiative (PGI) as a form of proactive coping strategy before childbirth, with gray matter volume after delivery. Childbirth is one of the few predictable major life-events, which, while being one of the most positive experiences for many, is also accompanied by multidimensional stress for the mother. Previous research has shown that high stress is associated with reductions in gray matter volume in limbic cortices as well as the prefrontal cortex (PFC). We hypothesized that personal growth initiative before childbirth is positively related to gray matter volume after delivery, especially in the ventromedial prefrontal cortex. In a prospective study, 22 first-time mothers answered questionnaires about their PGI level one month before birth (T1) and one month after delivery (T2). Four months after giving birth, a follow-up assessment was applied with 16 of these mothers (T3). Structural brain data were acquired at both postpartal measurement occasions. Voxel-based morphometry was used to correlate prenatal PGI levels with postpartal gray matter volume. Higher PGI levels before delivery were positively associated with larger gray matter volume in the ventromedial PFC directly after childbirth. Previous structural neuroimaging research in the context of major life events focused primarily on pathological reactions to stress (e.g., post-traumatic stress disorder; PTSD). The current study gives initial indications that proactive coping may be positively associated with gray matter volume in the ventromedial PFC, a brain region which shows volumetric reductions in PTSD patients.